Construction of a chiral zinc–camphorate framework for enantioselective separation. Issue 25 (15th June 2022) - Zhu, Chengfeng; Wang, Hongzhao; Mu, Yongfei; Zhang, Ziwei; Cheng, Lanjun; Li, Tianfu; Fu, Yanming; Wu, Xiang; Li, Yougui
Abstract : A chiral zinc–camphorate framework with accessible chiral pores and multiple recognition sites is constructed. Acting as a recyclable chiral host, it can resolve a variety of racemic alcohols and epoxides with excellent enantioselectivities. Abstract : A chiral metal–organic framework (CMOF) with open chiral channels and multiple recognition sites is constructed from camphoric acid and a dipyridyl ligand. It can act as an efficient chiral solid adsorbent, capable of separating a variety of racemic alcohols and epoxides with excellent enantioselectivities.